Effect of fermentation temperature and duration on chemical composition of Bush tea (Athrixia phylicoides DC.) - Hlahla, Linda Noble (My University, 2010)
A study was conducted to determine the effect of fermentation temperature and duration on chemical composition of bush tea (Athrixia phylicoides DC.). Bush tea was fermented in incubators at different temperatures and for different lengths of time for quality improvement. Treatments for fermentation temperature consisted of control (24°C; room temperature), 30°C, 34°C, 38°C and 42°C where the tea leaves were fermented for 30 minutes. Treatments for fermentation time consisted of control (0), 60, 90, and 120 minutes at an incubator temperature of 22-26°C. A completely randomized design (CRD) was used with three replicates for both evaluations. The chemical analysis (polyphenols, tannins and antioxidants) were done using Waterman and Mole (1994) method. The results of this study demonstrated that fermentation temperature significantly increases polyphenols at 30, 34, and 38°C whereas tannin content showed a great reduction at 38 and 42°C. Increasing fermentation time achieved a significant increase in both polyphenols (60 and 90 minutes) and tannin contents (90 and 120 minutes). However, changes in either fermentation temperature or time did not give any significant influence on antioxidant content of bush tea.
Thesis (M.Sc.) --University of Limpopo, Turfloop Campus, 2010
Keywords: Athrixia phylicoides DC; Fementation; Bush tea; 635.0968; Horticulture